Sphenopalatine Ganglion Blocks in Headache Management: A Review - Andrei Lyle Bautista; Killian Coyne; Alexander Bautista; Alaa Abd-Elsayed (Brain Sciences)
Headache disorders are among the most prevalent and disabling neurological conditions worldwide, affecting more than three billion individuals and contributing to a substantial socioeconomic burden. Despite the availability of pharmacologic treatments such as triptans, NSAIDs, and CGRP monoclonal antibodies, a significant proportion of patients remain refractory or intolerant to these therapies. The sphenopalatine ganglion (SPG), a parasympathetic neural structure in the pterygopalatine fossa, is increasingly recognized as a critical node in the pathophysiology of primary headache disorders. SPG blocks—using local anesthetics, neurolytic agents, or electrical neuromodulation—offer a minimally invasive therapeutic approach by disrupting nociceptive transmission and autonomic activation. This narrative review synthesizes the anatomical and physiological rationale for SPG intervention, details various procedural techniques, evaluates clinical evidence across headache subtypes, and explores future research directions. Conditions covered include migraine, cluster headache, tension-type headache, trigeminal neuralgia, and persistent idiopathic facial pain. With expanding evidence and evolving technologies, SPG-targeted interventions have the potential to reshape the management of refractory headaches and facial pain syndromes.